Extractive ethoxycarbonylation in high-temperature gas chromatography mass spectrometry based analysis of serum estrogens - Moon, Ju-Yeon; Kang, Se Mi; Moon, Myeong Hee; Hong, Jongki; Kim, Ki Tae; Jeong, Dae Hoon; Kim, Young Nam; Chung, Bong Chul; Choi, Man Ho (ELSEVIER, 2011)
A comprehensive gas chromatography-mass spectrometry (GC-MS)-based profiling was developed as a practical assay for quantification of 18 endogenous estrogens in serum samples. The present GC-MS method was conducted with the two-phase extractive ethoxycarbonlyation (EOC) of the phenolic hydroxy groups of estrogen with ethyl chlorformate combined with the non-polar n-hexane extraction. The subsequent perfluoroacylation of aliphatic hydroxy groups with pentafluoropropionyl anhydride (PFPA) was conducted. The serum samples were separated through a high temperature GC column (MXT-1) within an 8-min run and analyzed in selected-ion monitoring mode with good chromatographic properties for 18 estrogens as their EOC-PFP derivatives. The limit of quantification (LOQ) was 0.025-0.10 ng/mL for most estrogens analyzed except for E3 and 2-OH-E3 (0.5 ng/mL each). The devised method was found to be linear over a 10(3)-fold concentration range with a correlation coefficient (r(2) > 0.992), whereas the precision (% CV) and accuracy (% bias) ranged from 3.1 to 16.3% and from 93.5 to 111.1%, respectively. Decreased 2-methoxy-17 beta-estradiol levels were confirmed in patients with preeclampsia than healthy pregnant women. This technique can be used for a clinical diagnosis as well as understanding the pathogenesis in estrogen-related disorders. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: CATECHOL-O-METHYLTRANSFERASE; ESTRADIOL; ESTRONE; METABOLISM; CANCER; 17-BETA-ESTRADIOL; DEFICIENCY; CELLS; HAIR; RIA